2021
DOI: 10.1590/1980-549720210018.supl.2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviors and condom use in the Brazilian population: analysis of the National Health Survey, 2019

Abstract: Objective: The objective of this research was to describe the sexual behaviors and condom use in the Brazilian population. Methods: This is a cross-sectional, descriptive study, which used data from 88,531 individuals aged 18 years old or older, who answered the second edition of the National Health Survey carried out in 2019. Prevalence was estimated with the respective 95% confidence intervals for each sexual behavior indicator and condom use according to gender, age, race/skin color, educational level, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
1
9
0
13
Order By: Relevance
“…5 Moradores do Norte do país referem alta prevalência de múltiplos parceiros ocasionais, 6 comportamento este que pode estar associado ao maior uso de preservativo entre jovens. Mais um estudo transversal sobre comportamento sexual, este fundamentado em dados da mesma PNS 2019, 15 mostrou que o uso dos serviços de saúde para obter preservativos foi maior na região Norte. Contudo, tal associação deve ser analisada com cautela, uma vez que grupos mais favorecidos socioeconomicamente são menos dependentes dos serviços públicos de saúde para conseguir preservativos de forma gratuita.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…5 Moradores do Norte do país referem alta prevalência de múltiplos parceiros ocasionais, 6 comportamento este que pode estar associado ao maior uso de preservativo entre jovens. Mais um estudo transversal sobre comportamento sexual, este fundamentado em dados da mesma PNS 2019, 15 mostrou que o uso dos serviços de saúde para obter preservativos foi maior na região Norte. Contudo, tal associação deve ser analisada com cautela, uma vez que grupos mais favorecidos socioeconomicamente são menos dependentes dos serviços públicos de saúde para conseguir preservativos de forma gratuita.…”
Section: Discussionunclassified
“… 5 People living in the North of the country report high prevalence of multiple casual sex partners, 6 this being a behavior that may be associated with higher condom use among young people. Another cross-sectional study on sexual behavior, also based on 2019 PNS data, 15 showed that using health services to get condoms was higher in the Northern region. However, this association should be analyzed with caution, since more socioeconomically advantaged groups are less dependent on public health services for obtaining free condoms.…”
Section: Discussionmentioning
confidence: 99%
“…Several efforts have been made to improve the experience of using condoms (e.g., developing and testing new products; Beksinska et al, 2020;Coffey & Kilbourne-Brook, 2021;Gallo et al, 2022). However, recent reports worldwide show a high prevalence of STIs (Barbaric et al, 2022;Kreisel et al, 2021;Marcus et al, 2021;Sentís et al, 2021;Vives et al, 2020;Zheng et al, 2022), along with low condom use rates (Copen et al, 2022;Felisbino-Mendes et al, 2021;Fetner et al, 2020;Harper et al, 2018;Koumans et al, 2020;Lindberg et al, 2021). Inconsistent condom use may occur because condoms are mainly used for birth control and only seldom for protection against STIs (Milhausen et al, 2013).…”
Section: Portugal and Spainmentioning
confidence: 99%
“…A national survey carried out in 2019 verified that one out of five Brazilians uses condoms in all sexual relations, with the highest prevalence in the North region. However, it is also in this region that sexual initiation occurs at an increasingly early age, in males, with lower income and schooling levels 10 . Regarding the riverside population, a study identified STI prevalence of 20.8%, where riverside men are three times more likely to be infected, with some risk factors for male vulnerability being socioeconomic issues, sexual practice with sex workers and use of illicit drugs 11 .…”
Section: Introductionmentioning
confidence: 99%